The Effect of Implementing the Balanced Scorecard on The Strategy of Sustainable Development Applied to the Ain Shams University Specialized Hospital - Mustafa, Amal (The Arab Journal of Administration, 2022)
This research focuses on the importance of the tool the institution takes in evaluating its performance, so that its vision is comprehensive and its decisions are effective, on the basis that the successful performance evaluation and measurement process must interact with each of the environmental variables. And rapid developments. And the balance between short-term goals and long-term strategic goals Therefore, this study aimed to know the degree of using the Balanced Scorecard (BSC) dimensions as a tool to measure the performance of Ain Shams University Specialized Hospital and its impact on the application of sustainable development practices in the hospital under study, and Balanced Scorecard is defined as “translation of the organization’s mission and strategy into concrete goals and measurements through interaction Four axes are “the financial axis, the internal operations axis, the customer axis, and the growth and learning axis”. To achieve this purpose, the researcher used the descriptive analytical method, and questionnaire forms were randomly distributed to the members of the study sample consisting of gentlemen doctors. Hospital staff from (Professor - Assistant Professor - Assistant Teacher - Teacher - Teaching Assistant) The number of 280 individuals, and the questionnaire forms consist of two parts, the first part represents personal and functional information for the study sample individuals, the second part consists of questions to know the extent of applying the dimensions of the balanced performance card (as an independent variable), and questions to identify the application of the dimensions of sustainable development (as a dependent variable) in a hospital Ain-Shams University. The research concluded with a set of recommendations aimed at the importance of the effective role of the balanced scorecard in achieving the strategy of sustainable development and how this modern model contributes to achieving the university’s strategy 2018-2023 whose axes are based on innovation, knowledge, sustainable development and emanating from Egypt’s 2030 strategy and vision. conducting statistical analyzes.